Blood Meal Utilization as Organic Fe Source for Polka Dot Grouper Cromileptes altivelis Growth Performance - Mia Setiawati; P. Purnama; I. Mokoginta (Jurnal Akuakultur Indonesia)
This experiment was designed to examine the use of spray dried cell blood meal as organic Fe source in polka dot grouper (Cromileptes altivelis) feed to substitute inorganic Ferosulphate (FeSO4.7H2O). Two treatments were applied, one with FeSO4.7H2O as Fe source and the other with 6% blood meal. Fish with initial length and weight of 6.48 ± 0.16 cm and 5.60±0.25 g was reared at a density of 10 fish/aquarium (40 x 60 x 50 cm3) in a recirculation system for 40 days. Feed was administrated 3 times a day at satiation. The use of organic Fe with 6% blood meal apparently resulted in a lower body Fe content, feed consumption and lipid retention but a higher protein retention and feed efficiency. There was however no significant difference between treatments in growth and survival (P>0.05).